Implikasi Dan Tantangan Implementasi Hukum Pidana Internasional Di Era Globalisasi (Studi Kasus Genosida Rohingya Di Myanmar) - Ari Maulana; Defira Azar; Nadila Isna; Tri Kurnia; Herli Antoni (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
International criminal law refers to the legal system used to prosecute and punish individuals who commit international crimes, such as genocide, crimes against humanity, and war crimes. In the era of globalization, perpetrators of international crimes are increasingly difficult to account for because they often escape to other countries. Therefore, the application of international criminal law becomes increasingly important to uphold international justice and ensure that perpetrators of international crimes do not go unpunished. The implementation of international criminal law has important implications in upholding international justice and ensuring that perpetrators of international crimes do not go unpunished. However, there are many challenges in its application, especially in the complex era of globalization. The case study of the Rohingya genocide in Myanmar shows that there are many challenges that must be overcome in applying international criminal law, such as difficulties in extraditing perpetrators of international crimes and gathering sufficient and sufficient evidence to file charges at international courts.